VIRULENCE GENE PROFILING AND PATHOGENICITY OF Streptococcus agalactiae ISOLATED FROM TILAPIA, Oreochromis niloticus FARMS IN INDONESIA - Sukenda Sukenda; Achmad Suhermanto; Muhammad Zairin Jr.; Angela Mariana Lusiastuti; Sri Nuryati; Dendi Hidayatullah (Indonesian Aquaculture Journal, 2021)
Streptococcosis caused by Streptococcus agalactiae has become a major disease problem in tilapia culture in Indonesia. This study aimed to detect virulence genes of S. agalactiae during streptococcosis disease outbreaks in several tilapia farms in Indonesia and evaluate the correlation between biotype and virulence genes to bacterial virulence. The presence of virulence genes was determined in 10 strains of S. agalactiae isolated from farm-raised tilapia. Polymerase chain reaction (PCR) protocol was used to determine genes for cylE, hylB, lmb, bib A, PI-2b, fbs A, fbs B, gap, PI-1, and cfb in the template DNA. Pathogenicity test was carried out by intraperitoneal injection of 24 hour-cultured S. agalactiae to tilapia with 108 CFU/fish. Four isolates have seven of virulence genes (cylE, hylB, bibA, PI-2b, fbs A, fbs B, and gap genes), three isolates have six virulence genes (hylB, bib A, fbs A, fbs B, gap, cfb genes), one isolate has four virulence gene (hyl B, bib A, fbs, and cfb genes), and one isolate has one virulence gene (PI-2b gene). None of the isolates has lmb or PI-1 genes. Bacteria with more virulence genes showed higher pathogenicity post injection. Mortality of tilapia injected with b-hemolytic bacteria was 100% within the period of 14-19 hours, while non-hemolytic bacteria was 53.3%-86.6% on 14 days post-injection. Pathological changes associated with the infection by either isolate included melanosis, slow response, anorexia, ocular opacity, gasping, erratic, C-shape, and whirling. It can be concluded that S. agalactiae with more virulence genes show a higher level of pathogenicity. The presence of a virulent gene has the potential to be used as a basis for selecting candidate isolates and designing vaccine compositions as an effort to prevent streptococcosis infection in tilapia in Indonesia.